Malignant Insulinoma with Multiple Liver Metastases and Hypercalcitoninemia in a Patient with Type 2 Diabetes Mellitus Presenting as Recurrent Episodes of Diaphoresis due to Severe Hypoglycemia - Marco Ciacciarelli; Gianluca Caruso; Marco Rengo; Piero Maceroni; Carmen Misurale; Eleonora D’Armiento; Alessandro Polidoro; Cristina Napoli; Alberto Lombardini; Umberto Ceratti; Ruben Manuel Luciano Colunga Biancatelli; Leonardo Calvosa; et al. (Case Reports in Endocrinology)
Insulinoma is an insulin-producing pancreatic neuroendocrine tumor that can be malignant in about 10% of cases. Locoregional invasion, lymph node metastases, or remote metastases are the main criteria of malignant insulinoma. Its incidence in patients with pre-existing diabetes mellitus (DM) is exceptionally rare. In this report, we describe a 66-year-old man with long-standing type 2 DM who presented with recurrent episodes of diaphoresis due to severe hypoglycemia despite the withdrawal of insulin therapy, hypercalcitoninemia, and biochemical and radiological findings suggestive of metastatic malignant insulinoma. Unfortunately, after few days of diazoxide treatment, edema, hypotension, oliguria, and water retention were observed, patient’s clinical status deteriorated rapidly, and he died in our department from acute renal failure.